2021
DOI: 10.3390/microorganisms9010150
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Metabarcoding of Belowground Fungal Communities in Bare-Root Forest Nurseries: Focus on Different Tree Species

Abstract: The production of tree seedlings in forest nurseries and their use in the replanting of clear-cut forest sites is a common practice in the temperate and boreal forests of Europe. Although conifers dominate on replanted sites, in recent years, deciduous tree species have received more attention due to their often-higher resilience to abiotic and biotic stress factors. The aim of the present study was to assess the belowground fungal communities of bare-root cultivated seedlings of Alnus glutinosa, Betula pendul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 96 publications
(70 reference statements)
1
10
0
Order By: Relevance
“…The commercial expansion of the wood market reflected in the growth of the seedling market and, consequently, in enterprises suitable for the production and management of seedlings, characterized as forest nurseries [5].…”
Section: Introductionmentioning
confidence: 99%
“…The commercial expansion of the wood market reflected in the growth of the seedling market and, consequently, in enterprises suitable for the production and management of seedlings, characterized as forest nurseries [5].…”
Section: Introductionmentioning
confidence: 99%
“…Some notable potential pathogens from the results were Pythium, Fusarium, Botryosphaeriaceae, Microbotrytomycetes, Xanthamonadales, and Hyphomonas. Pythium and Fusarium are common fungi in bare-root forest nurseries [67]. What was remarkable about the presence of these possible pathogens in the Gold Creek results was the way that the putative pathogens may be controlled by antibiotic-producers that were found in high abundance on the various Trails.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a gathering body of evidence is demonstrating the introduction and spread of invasive Phytophthora species in California wildlands as the result of restoration schemes involving planted native species raised in contaminated nurseries [ 81 ]. Based on this conclusion, different recent studies focus on the identification of Phytophthora species in forest nurseries plantings using metabarcoding to implement stringent biosecurity practices when raising stocks of native plants destined for planting onto ecologically sensitive sites [ 82 , 83 ].…”
Section: Metabarcodingmentioning
confidence: 99%
“…Abad et al [ 90 ] reported that correct identification of Phytophthora to species levels in environmental DNA is possible targeting the full ITS rDNA via the miniaturized MinION portable device. Different studies on environmental fungal communities, that also includes Oomycetes , have been also performed with PacBio Sequencing [ 83 , 91 ], but no long-read sequencing method has been found to be applied specifically to Phytophthora genus.…”
Section: Metabarcodingmentioning
confidence: 99%